Large-Eddy Simulation of Unsteady Flow in a Mixed-Flow Pump - Chisachi Kato; Hiroshi Mukai; Akira Manabe (International Journal of Rotating Machinery)
This article describes the large-eddy simulation (LES) of the internal flows of a high–specific-speed, mixed-flow pump at low flow-rate ratios over which measured head-flow characteristics exhibit weak instability. In order to deal with a moving boundary interface in the flow field, a form of the finite-element method in which overset grids are applied from multiple dynamic frames of reference has been developed. The method is implemented as a parallel program by applying a domain-decomposition programming model.